Efektifitas Buku Audio dalam Meningkatkan Pengetahuan Kesehatan Reproduksi bagi Perempuan Penyandang Disabilitas Netra - Dewi Pramanik, Novita; Sri Rahayu, Eva; Sasnitiari, Ni Nyoman; Rizqi, M. Aris (Indonesian Journal Publisher, 2025)
Reproductive health is one of the indicators of a person's well-being. To achieve optimal reproductive health, of course, it begins with recognizing the reproductive organs. Background: There is still a lack of education for people with visual impairments regarding the anatomy of female genitalia and the menstrual cycle. Objective: to determine the effect of education using audio books regarding the introduction of reproductive organs and the menstrual cycle on the knowledge and attitudes of women with visual impairments. Method: The study was conducted in May-August 2024 in Bogor City, West Java Province. This study used a quasi-experimental design, with 31 respondents who could participate. Data collection was carried out by providing a pretest before providing education, and ending with a posttest. The analysis technique used the t-dependent test for the knowledge aspect and the Wilcoxon test for the attitude aspect. Results: there was a significant difference in the average knowledge between before and after education (p <0.05). In the attitude dimension, there was no significant difference between before and after education (p>0.05). Conclusion: Providing education about the anatomy of female genitalia and the menstrual cycle using audio books can improve the knowledge of women with visual impairments. Suggestions for further research is considering using more time to shape the attitudes of women with visual impairments in introducing the anatomy of female genitalia and the menstrual cycle so that they can be more aware of the importance of understanding this as an initial step in maintaining their reproductive health.